2003
DOI: 10.1093/jac/dkg072
|View full text |Cite
|
Sign up to set email alerts
|

Influence of population density on antibiotic resistance

Abstract: Antibiotic consumption and population density as a measure of crowding in the community were related to the prevalence of antibiotic resistance of three cities in three different countries: St Johns in Newfoundland (Canada), Athens in Greece and Groningen in The Netherlands. Antibiotic consumption was expressed in DDD (defined daily dose), as DID (DDD/1000 inhabitants/day) and as DSD (DDD/km(2)). The prevalence of antibiotic-resistant Escherichia coli and enterococci was determined in faecal samples of healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 18 publications
3
55
0
Order By: Relevance
“…Surveys have produced contradictory results, as different antibiotics appear to exhibit different selection powers [5,15]. Apart from antibiotic consumption, other factors such as the high turnover of respiratory pathogens in daycare centres, clonal spread of resistant strains, natural fluctuations and the high population density have all been held responsible for resistance [16].…”
Section: Discussionmentioning
confidence: 99%
“…Surveys have produced contradictory results, as different antibiotics appear to exhibit different selection powers [5,15]. Apart from antibiotic consumption, other factors such as the high turnover of respiratory pathogens in daycare centres, clonal spread of resistant strains, natural fluctuations and the high population density have all been held responsible for resistance [16].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the Tama River in Tokyo and the Cumberland River in Nashville, Tennessee (United States) showed that fecal bacteria concentrations, possibly originating from sewer overflows, were significantly affected by population density (Ham et al 2009;Young and Thackston 1999). An aggregated (or "ecological") study across three developed countries also found suggestive evidence that higher population density may be related to increased antibiotic resistance because higher interpersonal contact can lead to the spread of resistant bacteria (Bruinsma et al 2003).…”
Section: Background: Population Density Sanitation and Disease Extementioning
confidence: 99%
“…Several publications suggest a link between population density (and overcrowding) and the prevalence of antimicrobial resistance, 21,22 increasing the number of resistant bacteria circulating in the community and increasing the risk for cross-transmission between humans living in proximity. Urban areas, especially from the largest towns in Belgium, may cumulate several potential risk factors for import and dissemination of CPE: a high population density coupled with a dense healthcare network, concentration of university hospitals, larger proportion of immigrants, asylum seekers and refugees, and higher number of tourist travellers.…”
Section: Belgium a Country With A High Population Densitymentioning
confidence: 99%